Advantage of delivering the gene therapy tool (Cas9) as purified protein formulation - Doolaanea, Abd Almonem (OMICS International, 2017)
Gene editing permits the alteration of genomic sequences in vitro and in vivo, which could serve as a powerful tool in basic research and human gene therapy. The recent clustered regularly interspaced short palindromic repeat (CRISPR) system has revolutionized the way of gene editing. To be used in human, a suitable in vivo-compatible delivery form and method should be used. The delivery form here is meant ‘what’ is being introduced to the body: plasmid DNA, viral vector, mRNA, purified protein or other while the delivery method is meant ‘how’ the CRISPR system is introduced or administered: lipid transfection, electroporation, nanoparticles, liposomes or others. The brief discussion in this article suggests that delivering the protein component of the CRISPR system as purified protein has several advantages considering different sides like the industrial feasibility and pharmacokinetic/ pharmacodynamic aspects.